Criminological approaches to international criminal law / edited by Ilias Bantekas and Emmanuela Mylonaki. - Bantekas, Ilias; Mylonaki, Emmanouela (Cambridge University Press, 2014)
This volume is one of the few books to explain in-depth the international crimes behind the scenes of substantive or procedural law. The contributors place a particular focus on what motivates participation in international crime, how perpetrators, witnesses and victims see their predicament and how international crimes should be investigated at local and international level, with an emphasis on context. The book engages these questions with a broad interdisciplinary approach that is accessible to both lawyers and non-lawyers alike. It discusses international crime through the lens of anthropology, neuroscience, psychology, state crime theory and information systems theory and draws upon relevant investigative experience from experts in international and domestic law prosecutions.